Keutamaan Ilmu Dalam Jaringan Pendidikan Islam di Antara Johor dan Pahang Pada Abad ke 19M - Nurulwahidah Fauzi; Nor Adina Abd Kadir; Nurul Asiah Fasehah Muhamad; Siti Nor Baya Mat Yacob (Universiti Malaya, 2024)
Non-Indexed Publication